Teknologi Tepat Guna Pembuatan Recycle Planter Dan Tanaman Obat Keluarga (TOGA) - Ramli, Rimayang Anggun Laras Prastianty; Silalahi, Rudi Yanto Batara; Sumarna, Alfonsa Dian (Politeknik Negeri Batam, 2023)
Utilization of waste for recycling planting or known as a recycled planter, where one of the results is in the form of a plastic container that can be used as a medium for planting TOGA (in Indonesian: Tanaman Obat Keluarga) (family physic medical plants). The recycle planter and TOGA have economic value and health and support the go green program. Therefore, it is necessary to carry out an activity to introduce and practice the recycle planter and TOGA. This community service activity is carried out to provide a solution to this problem, where this service activity is carried out in three stages, namely 1) pre-field, 2) socialization, practice, and mentoring, and 3) report and publication preparation. This activity was carried out at RT 02 Tanjung Kertang Village, Galang District, Riau Archipelago Province. The results of this service are in the form of pot planters and TOGA products that can be used by residents. In addition, residents can also apply and practice how to make recycled planters and TOGA plastic containers